BURAKOVO-AGANOZERO LAYERED MASSIF OF THE TRANS-ONEGA REGION: 1. GEOCHEMICAL STRUCTURE OF THE LAYERED SERIES - Nikolaev G.S.; Khvorov D.M. (My University, 2003)
The paper presents an examination and interpretation of petrogeochemical data on the basis of the phase composition of cumulates. A new structural scheme of the Layered Series of the massif is proposed. The Layered Series shows an upsection change of zones of olivine, two-pyroxene, two-pyroxene-plagioclase, and magnetite-two-pyroxene-plagioclase cumulates. This change corresponds to the succession of the typomor- phic cumulus assemblages, which, in the first approximation, can be taken as the crystallization order of pri- mary magma. It was demonstrated that the rocks formed simultaneously in different parts of the magmatic chamber with diverse geochemical features determined by different porosities of cumulus frameworks. The zone of two-pyroxene cumulates is complicated by a peridotite horizon and a leucogabbro-anorthosite layer, with the former produced by injection of a new magma portion. The spatial relation of leucogabbros and anorthosites to the rocks affected by the strongest subsolidus alteration (monomineral clinopyroxenites) sug- gests that they crystallized within one chamber.